Perception and Cognition in the Ageing Brain: A Brief Review of the Short- and Long-Term Links between Perceptual and Cognitive Decline - Roberts, Katherine L.; Allen, Harriet A. (Frontiers in Aging Neuroscience, 2016)
Ageing is associated with declines in both perception and cognition. We review evidence for an interaction between perceptual and cognitive decline in old age. Impoverished perceptual input can increase the cognitive difficulty of tasks, while changes to cognitive strategies can compensate, to some extent, for impaired perception. While there is strong evidence from cross-sectional studies for a link between sensory acuity and cognitive performance in old age, there is not yet compelling evidence from longitudinal studies to suggest that poor perception causes cognitive decline, nor to demonstrate that correcting sensory impairment can improve cognition in the longer term. Most studies have focused on relatively simple measures of sensory (visual and auditory) acuity, but more complex measures of suprathreshold perceptual processes, such as temporal processing, can show a stronger link with cognition. The reviewed evidence underlines the importance of fully accounting for perceptual deficits when investigating cognitive decline in old age.